Thermoacoustic resonance effect and circuit modelling of biological tissue - Gao, Fei (2013)
In this letter, thermoacoustic resonance effect is predicted from theoretical analysis with series resistor-inductor-capacitor resonance circuit model and then observed experimentally using muscle tissue illuminated by multi-pulse microwave source. Through model fitting, the circuit parameters are extracted to characterize quantitatively the resonant response of the tissue. Coherent demodulation is applied to obtain the enhanced signal-to-noise ratio and spatial information by treating tissue as a communication channel. This physical phenomenon shows significantly higher sensitivity than conventional single microwave pulse induced thermoacoustic effect, enabling the potential design of low-power thermoacoustic imaging device for portable and on-site diagnosis.